2005
DOI: 10.1080/03079450500178824
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between live avian pneumovirus and Newcastle disease virus vaccines in specific pathogen free chickens

Abstract: One-day-old specific pathogen free White Leghorn chicks were vaccinated with live avian pneumovirus (APV) vaccine, live Newcastle disease virus (NDV) vaccine or both. At intervals up to 28 days after vaccination, distribution of the virus in the tissues was studied, together with humoral and mucosal antibody responses in lachrymal fluid and tracheal washes. APV vaccine was detected for almost twice as long in the dual vaccinates as in the single vaccinates. Higher numbers of isolations of ND virus vaccine were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
3
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 18 publications
2
25
3
1
Order By: Relevance
“…Although we did not perform virus isolation from the different tissue samples, a very high positive correlation between virus isolation and RT-PCR detection that validates the use RT-PCR for NDV tissue tropism studies has been reported (Gohm et al, 2000; Ganapathy et al, 2005;Wakamatsu et al, 2007). An association between the site of replication and the levels of IgA production was observed and can be explained by the virus replication and host antigen recognition mechanisms proposed for NDV (Peeters et al, 1999;Alexander, 2001;de Leeuw et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not perform virus isolation from the different tissue samples, a very high positive correlation between virus isolation and RT-PCR detection that validates the use RT-PCR for NDV tissue tropism studies has been reported (Gohm et al, 2000; Ganapathy et al, 2005;Wakamatsu et al, 2007). An association between the site of replication and the levels of IgA production was observed and can be explained by the virus replication and host antigen recognition mechanisms proposed for NDV (Peeters et al, 1999;Alexander, 2001;de Leeuw et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work (Ganapathy et al, 2005, it was demonstrated that when live aMPV and VG/GA vaccines were given simultaneously to day-old SPF chicks, the efficacy of the vaccines was not affected. In addition, local and humoral immune responses in SPF (Cook et al, 2001;Ganapathy et al, 2005Tarpey et al, 2007) and broiler chicks (Ganapathy et al, 2006) have been reported before.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, live and inactivated vaccines for aMPV control and prevention were only available in the last two decades and restricted to certain countries (Cook, 2000;Cook and Cavanagh, 2002;Alexander and Jones, 2008). It was reported that when live aMPV and ND virus (NDV) vaccines were given in combination in day-old chicks, both singly and dually vaccinated chicks were equally protected against aMPV challenge (Ganapathy et al, 2005. In addition, protection against virulent NDV was not affected in single and dual vaccination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Humoral immunity of bird URT is associated mainly with sIgA, and its protective role has been demonstrated based on several poultry respiratory infections (Jayawardane and Spradbrow 1995, Ganapathy et al 2005, Van Ginkel et al 2008). Up to date, little is known about the role of sIgA in the protection against TRT.…”
Section: Discussionmentioning
confidence: 99%